Perlindungan Hukum Bagi Para Pihak Dalam Perjanjian Leasing di Indonesia - Tradesa, Anggi; M. Jihan Febriza (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2026)
This study aims to analyze the forms of legal protection for the parties, particularly the lessee, in leasing agreements in Indonesia, as well as examine the legal protection mechanisms in ensuring legal certainty and justice in leasing financing practices. This study uses a normative legal method, which views law as written norms in legislation and legally binding behavioral guidelines. The research approach includes a statutory approach and a conceptual approach to understand relevant legal concepts. Primary, secondary, and tertiary legal materials are processed through inventory, classification, and systematization to facilitate analysis. The analysis is conducted using grammatical, systematic, and teleological legal interpretations, as well as legal theories and principles as analytical tools to assess the forms and mechanisms of legal protection. The results show that legal protection in leasing agreements is sourced from the Civil Code, OJK regulations, and the Consumer Protection Law, but standard agreement practices still place the lessee in a weaker bargaining position. Preventive and repressive mechanisms are available, but their effectiveness is limited, so legal protection must be designed in an integrative manner to ensure contractual certainty, balance, and justice.